Evaluating service quality of Multimodal Transportation Hub (MMTH) in Delhi, India: A gender-based perspective. Issue 2 (June 2022) - Chauhan, Vivek; Gupta, Akshay; Parida, Manoranjan
Highlights: Paper explores gender heterogeneity while assessing service quality (SQ) of MMTH. SEM is used to show separate SQ models for females and males. For females, safety & security is accounted the most impactful latent construct. For males, transfer environment & facilities construct is the most influencing one. Abstract: Gender has been recognized as the important demographic variable in the segmentation and categorization of the requirements of the users in the field of transportation and helps to identify the factors which are feasible in terms of achieving greater user satisfaction and better service quality of Multimodal Transportation Hub (MMTH). MMTH provides assistance in integrating and coordinating various modes of transport which helps in the decongesting of roads, providing better transfer environment, saving journey time, and ultimately, promotes sustainability. The present research attempts to evaluate the role of gender heterogeneity in the assessment of service quality of an identified MMTH in Delhi through user satisfaction survey with 515 samples. Total 6 latent factors were identified for measuring the MMTH's service quality. Substantial gender diversification was observed in the 'safety & security' construct through ANOVA test. 'Transfer environment & facilities' and 'safety & security' turned to be the most impactful latent constructs for males and females, respectively by deploying Structural Equation Modelling. Outcomes of the study will be useful for designing sustainable transport and gender-specific policies while analyzing MMTH's service quality and promoting gender equity in the field of public transportation.